ANALISIS POLA MANAJEMEN LABA DISEKITAR PERGANTIAN DIREKSI, DEWAN KOMISARIS DAN KOMITE AUDIT (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di BEI periode 2009-2013) - Idayu Rahmadewi; Puji Harto (Diponegoro Journal of Accounting, 2015)
This study investigates the differences in the pattern of earnings management in the period before the change, during the period of the change and the period of one year after the change of CEO, board of directors and audit committee. This study uses population of non-financial companies listed on the Stock Exchange during the period 2009-2013.Sample in this study was determined by purposive sampling method. Earnings management in this study was measured using discretionary accruals by Modified Jones Model. In this study, used the Wilcoxon rank signed test as analytical technique. The analysis showed that the significant differences in the pattern of earnings management at the change of the audit committee between the period before the change and the period after the change the audit committee and the significant differences in the pattern of earnings management at the the change year period and in the period after the change the audit committee. Differences in the pattern of earnings management around the change directors and commissioners did not show significant results.